Criteria for early diagnosis of third molar agenesis: a retrospective radiographic study - Margaux DUMAS; Pedro MARIANO-PEREIRA; Iman BUGAIGHIS; Paulo FERNANDES-RETTO; Luís PROENÇA (Dental Press Editora, 2023)
ABSTRACT Objective: To explore the association between chronological, dental and skeletal ages and early diagnosis of third molars agenesis. Material and Methods: This retrospective radiographic study comprised a sample of 282 Portuguese patients (122 males and 160 females) who sought orthodontic treatment between 2007 and 2018. Each participant had panoramic and lateral cephalometric radiographs performed before and after the age of 14 years. The chronological age was categorized into three intervals between 11.0 and 13.11 years of age. The full eruption of the four-second molars was used as a criterion in determining dental age. Skeletal age was verified by the vertebral maturation method. The diagnosis of agenesis of third molars was initially performed by observation of the initial panoramic radiography undertaken before the age of 14 years. Subsequently, the diagnosis of agenesis of third molars was confirmed by visualizing the second panoramic radiography, obtained after the age of 14 years. The association between the accuracy of the diagnosis and the chronological, dental and skeletal ages was evaluated using the chi-square test, at a 5% significance level. Results: No significant association between chronological age and alterations in the diagnosis of third molar agenesis was identified. However, there was a significant association between third molar agenesis and both dental age (p<0.001) and skeletal age (p=0.006). Conclusion: The eruption of the four-second molars and the peak of growth could be considered as criteria for early diagnosis of third molar agenesis, whereas chronological age is not a reliable diagnostic indicator.